1985
DOI: 10.1247/csf.10.327
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein phosphatase inhibits flagellar movement of Triton models of sea urchin spermatozoa.

Abstract: For several years much attention has been paid to the control of flagellar and ciliary movement in eukaryotes by the cyclic nucleotide system. Morton et al. (24) reported that flagellar movement of hamster cauda epididymal spermatozoa could be induced by diluting the semen with a medium containing calcium and that the initiation of beat was accompanied by an increase in the concentration of cyclic AMP within the cells. Garbers et al. (8) and Hoskins (14) reported that cyclic AMP or inhibitors of cyclic nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…With the known exception of carp sperm (Krasznai et al, 2000), phosphorylation on some axonemal proteins by cAMP-dependent kinase is required for initiation of sperm motility including that of sea urchins (Ishiguro et al, 1982;Brokaw, 1984Brokaw, , 1987aTakahashi et al, 1985;Murofushi et al, 1986;Bracho et al, 1998). It should be noted that cAMP is elevated by 1.9 fold upon dilution from low-pH ASW to Na + -free, Ca 2+ -free ASW added with amine (Beltrán et al, 1996), conditions similar to the present.…”
Section: Discussionsupporting
confidence: 69%
“…With the known exception of carp sperm (Krasznai et al, 2000), phosphorylation on some axonemal proteins by cAMP-dependent kinase is required for initiation of sperm motility including that of sea urchins (Ishiguro et al, 1982;Brokaw, 1984Brokaw, , 1987aTakahashi et al, 1985;Murofushi et al, 1986;Bracho et al, 1998). It should be noted that cAMP is elevated by 1.9 fold upon dilution from low-pH ASW to Na + -free, Ca 2+ -free ASW added with amine (Beltrán et al, 1996), conditions similar to the present.…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that the addition of a crude or partially purified protein phosphatase preparation from bovine cardiac muscle or rabbit skeletal muscle inhibits the motility of demembranated sea urchin spermatozoa, presumably due to its ability to cause dephosphorylation of axonemal proteins [28,29]. However, it has not been clear what kind of protein phosphatases are involved.…”
Section: Discussionmentioning
confidence: 99%
“…A similar protein factor called axokinin has been found in mammalian sperm and shown to induce the flagellar movement of Triton-extracted sperm (22,23). Furthermore, dephosphorylation in the Triton-extracted sea urchin sperm catalyzed by a phosphoprotein phosphatase from bovine cardiac muscle, was shown to reduce the motility of the Triton-extracted sperm (21). From these observations, it is suggested that the cAMP-dependent phosphorylation is important for activation or initiation of flagellar motility.…”
Section: Discussionmentioning
confidence: 82%
“…cAMP-dependent protein phosphorylation and dephosphorylation may be an important regulator of the flagellar movement in the Triton-extracted sea urchin sperm (4,11,16,21).…”
mentioning
confidence: 99%